Comparison of analgesic effects of gabapentin and paracetamol post-operatively in patients with hand injury - Hyder Ali; Naveed; Bushra Perveen (Journal of the Pakistan Medical Association, 2021)
Objective: Compare the analgesic effects of Gabapentin and Paracetamol post-operatively in patients with hand injury. Methods: This double blind, randomized control trial was conducted at the Department of Plastic Surgery, Dow University of Health Sciences Karachi; during March to August 2019. Fifty participants with hand injury and age ranged 18-60 were enrolled through consecutive sampling; while patients with multiple traumas, psychiatric illnesses, epileptic and pregnant were excluded. Informed written consent was obtained before enrollment of participants. Participants were randomly divided into two groups. Gabapentin (600 mg) and Paracetamol (1000 mg) were provided through anonymous packaging. Pain intensity was assessed using Visual Analogue Scale (VAS) along with self-designed questionnaire which was filled twice post-operatively (first at the time of drug intake once orally allowed and 6 hours later). Computer software SPSS 22 was used for analysis and comparison of results. Results: The analgesic effects of both the groups were analyzed using paired ‘t’ test which revealed statistically significant value i.e. <0.001 for each group. Though; the correlation coefficient was slightly more promising towards Paracetamol group (0.873 and 0.743 for Paracetamol and Gabapentin respectively). While in Gabapentin group there were more change of peaks were observed. Clinically more side effects were found in Gabapentin group. Conclusion: Both the drugs were found to be effective in pain management but Paracetamol had better pain control with relatively less side-effects. Key words: Pain, Hand injury, Gabapentin, Paracetamol. Continuous...